(untitled) (AU Library Scholarly Publishing Services, 2018)
This report presents the results of the Data Management i Praksis (DMiP) project (in English: Data Management in Practice). The project was funded by Denmark’s Electronic Research Library (DEFF), the National Danish Archives and the participating main Danish libraries. The following partners participated in the project: Aalborg University Library, Danish e-Infrastructure Cooperation (DeIC), DTU Library, Roskilde University Library, The Danish National Archives, Royal Danish Library and The University Library of Southern Denmark. The general objective of the project was to establish a Danish setup covering all aspects of the lifecycle of research data: from application, through the research phase, and finally to the dissemination of results and sharing of research data. The setup was to be based on researchers’ demands, and the suggestions and results of the project were to be at an international level. The project should also demonstrate that research libraries have a role to play regarding research data. Furthermore, the project should ensure development of competences at the libraries, which can then be used in the future process of managing research data.